Are We Doing More Than We Know? Possible Mechanisms of Response to Music Therapy - Clements-Cortes, Amy; Bartel, Lee (Frontiers in Medicine, 2018)
Due to advances in medical knowledge the population of older adults struggling with issues of aging like Alzheimer’s disease (AD), Parkinson’s disease (PD), and Stroke is growing. There is a need for therapeutic interventions to provide adaptive strategies to sustain quality of life, decrease neurologic impairment, and maintain or slow cognitive decline and function due to degenerative neurologic diseases. Musical interventions with adults with cognitive impairments have received increased attention over the past few years, such as the value of personalized music listening in the iPod project for AD (1); music as a tool to decrease agitation and anxiety in dementia (2); and music to aid in episodic memory (3); Rhythmic Auditory Stimulation as rehabilitation for PD (4); and recently the potential of 40Hz sensory brain stimulation with AD and PD (5-6). These approaches indicate the expanding scope and efficacy of music therapy and the potential mechanisms involved. This paper explicates a four-level model of mechanisms of music response (7-8) that may help understand current music therapy approaches and treatments and help focus future research. Each level will be illustrated with research and suggestions for research directions.